Utility of Blue Light Cystoscopy for Post-bacillus Calmette-Guérin Bladder Cancer Recurrence Detection: Implications for Clinical Trial Recruitment and Study Comparisons. Issue 3 (25th March 2022) - Chappidi, Meera R.; Yang, Heiko; Meng, Maxwell V.; Bivalacqua, Trinity J.; Daneshmand, Siamak; Holzbeierlein, Jeffrey M.; Kaimakliotis, Hristos Z.; Konety, Badrinath; Liao, Joseph C.; Pohar, Kamal; Steinberg, Gary D.; Taylor, Jennifer M.; et al.
Abstract : Purpose: The utility of blue light cystoscopy (BLC) in patients receiving bacillus Calmette-Guérin (BCG) during post-treatment cystoscopy is not well understood. Our objective was to determine if BLC improves recurrence detection in patients with non-muscle invasive bladder cancer (NMIBC) undergoing BCG. Materials and Methods: Using the prospective multi-institutional Cysview® Registry (2014–2019), patients with NMIBC who received BCG within 1 year prior to BLC were identified. Primary outcomes were recurrences and whether lesions were detected on white light cystoscopy (WLC), BLC or both. We calculated the percentage of cystoscopies with recurrences that were missed with WLC alone. The cystoscopy-level BLC false-positive rate was the proportion of cystoscopies with biopsies only due to BLC suspicious lesions without recurrence. Results: Of 1, 703 BLCs, 282 cystoscopies were in the analytic cohort. The overall recurrence rate was 45.0% (127). With only WLC, 13% (16/127) of recurrences would have been missed as 5.7% (16/282) of cystoscopies performed had recurrence only identified with BLC. Among 16 patients with recurrence missed with WLC, 88% (14) had carcinoma in situ. The cystoscopy-level BLC false-positive rate was 5% (15). Conclusions: BLC helped detect recurrences after recent BCG that would have been missed with WLC alone. Providers should consider BLC for high-risk patients undergoing BCG and should discuss the risk of false-positives with these patients. As clinical trials of novel therapies for BCG-unresponsive disease increase and there are no clear guidelines on BLC use for post-treatment cystoscopies, it is important to consider how variable BLC use could affect enrollment in and comparisons of these studies.